Pengaruh Karakteristik Pekerjaan, Organisasi Dan Individu Terhadap Kinerja Karyawan (Studi kasus pada resto MR.M4T Kota Malang) - Muhammad Al Akbar; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of carrying out research is to analyze the effect of job characteristics, organizational characteristics and individual characteristics on employee performance at the MR.M4T restaurant. The population in this study were 37 employees of the MR.M4T restaurant. With a saturated sampling technique, all members of the population were sampled. Using multiple linear regression analysis, and the results of the study show the effect of job characteristics, organizational characteristics, and individual characteristics has a significant effect on employee performance. The method used in processing data using a quantitative approach with multiple linear regression analysis tools through the IBM SPSS 25 application program (statistical product and service solutions). Keywords: Job Characteristics, Organizational Characteristics, Individual Characteristics, and Employee Performance